Authority of the Audit Board of the Republic of Indonesia in Examining Regional Government Performance - Dian Puspita Warih (Universitas Negeri Semarang, 2018)
Performance audits (performance audits) are carried out due to public dissatisfaction with financial audits which only assess the fairness of financial statements. Performance checks are also carried out because many government performances are often in the public spotlight due to the large number of reports regarding cases of corruption, collusion and nepotism (KKN). So there is a need for research on performance audits conducted by the Audit Board of the Republic of Indonesia (BPK). The purpose of this study is to describe the implementation of the authority of the BPK Representative Office of Central Java Province in examining performance from aspects of economy, efficiency and effectiveness and to describe the division of tasks between BPK as an external auditor and the Government Internal Supervisory Apparatus (APIP) as an Internal Auditor in carrying out performance audits. . This study uses a qualitative approach with the type of Juridical Sociological research. Data collection techniques include interviews and document studies with BPK representatives of Central Java Province and DPRD Central Java Province. The performance audit is carried out by the BPK Representative for Central Java Province in semester 2 (July-November) in three stages, namely the audit planning stage, the audit implementation stage and the performance inspection reporting stage and providing recommendations. It can be seen that the results of performance audits in the Regional Government of Central Java Province have met the economic, efficiency and effectiveness aspects. The economic aspect is based on the fulfillment of criteria that have been determined and mutually agreed upon by the BPK and the Regional Government. The efficiency aspect is based on the fact that the local government has optimally used the available inputs so that the expected goals are achieved. The aspect of effectiveness can be seen from the limitations of the budget deficit and the budget allocation in the regional budget regulation in accordance with applicable regulations. The division of tasks between BPK and APIP is contained in the implementation of performance checks and follow-up. BPK conducts performance checks and provides recommendations, then APIP uses its internal oversight and guidance function to follow up on the recommendations made by BPK to entities. Through the existence of APIP, it can be seen that BPK is greatly assisted in the process of carrying out performance audits.